INNOVATIVE 21ST-CENTURY CURRICULUM BASED ON LOCAL GENIUS 6.0: SYNERGY OF LOCAL WISDOM AND DIGITAL TRANSFORMATION IN INDONESIAN EDUCATION - Pertiwi, Santhi; Sumaryono, Agustinus; Madhakomala, Madhakomala (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the integration of 21st-century curriculum and the Local Genius 6.0 concept in building an educational system that responds to global demands without abandoning local cultural roots. Employing a literature review method, the study analyzes various academic sources and educational policies concerning curriculum design, digital learning resources, authentic assessment systems, and the role of local wisdom in the learning process. The findings reveal that the 21st-century curriculum emphasizes the development of critical thinking, creativity, collaboration, and communication competencies, supported by technology and project-based learning. Meanwhile, Local Genius 6.0 emerges as a contextual approach that integrates local cultural values into digital media to foster meaningful and character-based learning. The integration of both frameworks produces an innovative curriculum model with a glocal character—anchored in local wisdom while being responsive to global challenges. Furthermore, this curriculum aligns with the dimensions of the Pancasila Student Profile, fostering learners who are adaptive, competitive, and deeply rooted in national identity.